Rekruitmen Politik Dalam Pilkada di Kabupaten Takalar - Napir, Suaib (Faculty of Social and Political Science Universitas Brawijaya, 2018)
Political recruitment In local leaders election in this study get with qualitative method and descriptive analysis towards the manajemen and sympathizers Nasdem Takalar, Kitta- Syamsari-Achmad Dg. Sere partners, and regional general elections comminsions Takalar Regency. Syamsari Kitta-Achmad Dg Seers partner carried by PKS (4 seats) in partnership with the National Democratic or Nasdem party (2 seats) in local leaders election in Takalar Regency for the period 2017-2022. Both parties agreed that the couple could bring change in Takalar District. PKSs choice of Syamsari Kitta was due to its capacity, basis and electability, while Ahmad Daeng Sere was chosen as a vice regent candidate because he had positive electability to fight incumbents. In addition, Syamsari Kitta is also a PKS cadre who has political experience, her character is known to be simple, easy to get along with and communicate with the community and has a militant electoral base, both PKS cadres and other winning teams.